ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANIPISANG DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Muhammad Iqbram Aditya Nata; Teguh Endaryanto; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this research were to analyze the income of banana farmer households, the level of banana farmer household’s welfare, and the factors that influence the banana farmer household’s welfare. This research was conducted at Sumbermulyo and Tegalbinangun villages of Sumberejo subdistrict ofTanggamus regency. The samples were chosen by simple random sampling method. The number of respondents in this study was 62 banana farmers. The data were collected in March 2019. The method of data analysis used in this study was quantitative and qualitative descriptive analysis. The results showed that average household income of banana farmers in Sumberejo of Tanggamus Regency was IDR32,763,337.90 per year. It came from banana farming (on farm) amounting to IDR17,497,289.52 and from outside the banana farming (on farm, off farm and non farm) amounting to IDR15,266,048.38. Based on BPS (2014) criteria, banana farmers household at Sumberejo District were mostly categorized as prosperous farmers families. Based on the regression analysis using binary logit there were two factors influencing the prosperity grade of banana farmers, they are household income and the number of family members.Key words: banana farmers, farmer household’s welfare, income